Income Testing the Tax Threshold - Whiteford, Peter (UNSW Sydney, 1988)
This paper discusses some recent proposals to replace the tax threshold or zero step in the income tax rate scale with incometested tax rebates. The paper outlines the rationale for current arrangements and shows how they have developed over the past twenty years. The paper then evaluates the specific proposals made most notably by the Centre of Policy Studies at Monash University, in terms of their redistributive effects and implications for effective marginal tax rates and work incentives.
Social Welfare Research Centre discussion papers; 6
Keywords: Income tax; Tax thresholds